KH. Hasyim Asy’ari’s Educational Thought in the Context of Islamic Educational History: An Analysis of the Tradition and Transformation of Islamic Boarding Schools - Bayu Mahendra, Viki (Universitas Yudharta Pasuruan, 2025)
This study addresses the limited historical-analytical discussion of KH. Hasyim Asy’ari’s educational thought within the broader development of Islamic education in Indonesia, particularly in relation to the tradition and transformation of pesantren. The research aims to analyze KH. Hasyim Asy’ari’s educational ideas by situating them in the historical context of Islamic education and examining their contribution to the continuity and change of pesantren institutions. Employing a qualitative method with a historical approach and library research design, the study draws on primary sources, notably Adab al-‘Ālim wa al-Muta‘allim, as well as relevant secondary literature on Islamic education and pesantren history. The findings reveal that KH. Hasyim Asy’ari’s educational thought emphasizes adab, ethical teacher–student relations, and the integration of religious knowledge as the core of Islamic education. Furthermore, the study demonstrates that the transformation of pesantren—covering curriculum development, learning methods, and institutional management—represents a form of continuity rather than a rupture from tradition. KH. Hasyim Asy’ari’s ideas provide a conceptual foundation that enables pesantren to remain rooted in Islamic tradition while adapting to socio-historical changes. This research contributes to Islamic education studies by bridging the gap between classical ulama thought and the historical dynamics of pesantren transformation.